Serological and PCR-based markers of ocular Chlamydia trachomatis transmission in northern Ghana after elimination of trachoma as a public health problem. - Laura G Senyonjo; Oscar Debrah; Diana L Martin; Adwoa Asante-Poku; Stephanie J Migchelsen; Sarah Gwyn; Dzeidzom K deSouza; Anthony W Solomon; David Agyemang; Nana Biritwum-Kwadwo; Benjamin Marfo; Didier Bakajika; et al. (Public Library of Science (PLoS), 2018)
BACKGROUND:Validation of elimination of trachoma as a public health problem is based on clinical indicators, using the WHO simplified grading system. Chlamydia trachomatis (Ct) infection and anti-Ct antibody responses (anti-Pgp3) have both been evaluated as alternative indicators in settings with varying levels of trachoma. There is a need to evaluate the feasibility of using tests for Ct infection and anti-Pgp3 antibodies at scale in a trachoma-endemic country and to establish the added value of the data generated for understanding transmission dynamics in the peri-elimination setting. METHODOLOGY/PRINCIPAL FINDINGS:Dried blood spots for serological testing and ocular swabs for Ct infection testing (taken from children aged 1-9 years) were integrated into the pre-validation trachoma surveys conducted in the Northern and Upper West regions of Ghana in 2015 and 2016. Ct infection was detected using the GeneXpert PCR platform and the presence of anti-Pgp3 antibodies was detected using both the ELISA assay and multiplex bead array (MBA). The overall mean cluster-summarised TF prevalence (the clinical indicator) was 0.8% (95% CI: 0.6-1.0) and Ct infection prevalence was 0.04% (95%CI: 0.00-0.12). Anti-Pgp3 seroprevalence using the ELISA was 5.5% (95% CI: 4.8-6.3) compared to 4.3% (95%CI: 3.7-4.9) using the MBA. There was strong evidence from both assays that seropositivity increased with age (p<0.001), although the seroconversion rate was estimated to be very low (between 1.2 to 1.3 yearly events per 100 children). CONCLUSIONS/SIGNIFICANCE:Infection and serological data provide useful information to aid in understanding Ct transmission dynamics. Elimination of trachoma as a public health problem does not equate to the absence of ocular Ct infection nor cessation in acquisition of anti-Ct antibodies.